Diffuse large B-cell lymphoma in adults aged 75 years and older: a single institution analysis of cause-specific survival and prognostic factors. (December 2013) - Smith, Stephen D.; Chen, Andy; Spurgeon, Stephen; Okada, Craig; Fan, Guang; Dunlap, Jennifer; Braziel, Rita; Maziarz, Richard
Background: Very elderly patients (75 years and older) with diffuse large B-cell lymphoma (DLBCL) will be increasingly considered for cancer treatment as the population ages, but are underrepresented in clinical trials. Here we report outcomes of very elderly DLBCL patients treated in the modern era at the Oregon Health and Science University (OHSU). Methods: We queried the OHSU Tumor Registry for DLBCL cases treated since 2002. A total of 73 patients aged 75 years or older were analyzed under Institutional Review Board approval. Results: With a median follow up of 31 months, cause-specific survival was 58% and overall survival 51% at 3 years. Incorporation of an anthracycline did not influence outcomes. More than one extranodal site or poor-risk disease by Revised International Prognostic Index score were adversely prognostic, but pathologic features studied were not. Conclusions: Very elderly patients with DLBCL require prospective studies, which employ novel risk stratification and therapeutic approaches.